Surface modification of Ti6Al4 V implants by heat, H2O2 and alkali treatments. (2nd October 2016) - Khodaei, M.; Meratian, M.; Shaltooki, M.; Hashemibeni, B.; Savabi, O.; Razavi, M.
Abstract : In the present research we have applied three types of surface modifications on Ti6Al4 V alloy including heat treatment, H2 O2 treatment and alkali treatment. Scanning electron microscope and thin-film X-ray diffractometry (TF-XRD) were used to analyse the surface structure and the formed phases on the surface modified specimens. In vitro bioactivity evaluations were carried out and the cytocompatibility assay was performed using the evaluation of viability and attachment of L-929 fibroblast cells. The results revealed more bioactivity of the alkali-treated Ti6Al4 V alloy compared to other surface modifications. Better cellular response was also observed on the alkali-treated specimens. According to the results of our study, alkali treatment enhanced the in vitro bioactivity and cytocompatibility of Ti6Al4 V alloy more effectively than H2 O2 treatment and heat treatment.